Buya Hamka’s Historical thought and its Relevance to Islamic Education in Indonesia - Novia Regina Cahyani; Mila Yunita; Tita Agustin; Neneng Kasihati (Universitas Islam Negeri Sumatera Utara, 2026)
This study aims to analyze Buya Hamka’s historical thought, identify the educational values contained within it, and explain its relevance to Islamic education in Indonesia. The research employed a qualitative approach through library research. Data were collected from Buya Hamka’s works and various relevant academic sources and analyzed using content analysis and descriptive-analytical methods. The findings reveal that Hamka viewed history not merely as a record of past events but as a means of understanding Sunnatullah, developing human awareness, and drawing lessons for life. His historical thought is founded on three main principles: tawhid as a spiritual foundation, reason as an instrument for critically and objectively understanding historical facts, and morality as the primary value derived from historical events. The educational values embedded in this perspective include strengthening faith, fostering noble character, encouraging critical thinking, promoting exemplary conduct, developing responsibility, and building awareness in shaping civilization. The study concludes that Buya Hamka’s historical thought remains highly relevant to Islamic education in Indonesia, particularly in nurturing learners who possess knowledge, strong character, and a balanced integration of intellectual, spiritual, and moral dimensions amid the challenges of modernization.